MEDIA AUDIOVISUAL SEBAGAI MEDIA KOMUNIKASI DAN KREATIVITAS GENERASI MUDA - Suryanto, Hari (Institut Seni Budaya Indonesia Bandung, 2018)
At present the relationship between the younger generation and audio and visual media is getting stronger. The growth of film communities in the regions and the development of the education world of Vocational High School Organizing Record Media majors is evidence that the younger generation is very interested in media and technology, the emergence of the phenomenon of YouTubeers to be strong evidence of how audio and visual media become creative ways of delivering messages. Film-community work and students in several regions use the theme of potential culture, tourism, customs and events that occur in their environment. Unique citizen-based journalism as an interesting way of communicating.